2018
DOI: 10.3899/jrheum.161216
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Crohn Disease in Patients with Spondyloarthropathy: The SpACE Capsule Study

Abstract: Objective.Inflammatory bowel disease (IBD) is generally reported to be associated with spondylarthropathies (SpA) in 5%–15% of cases. Systematic colonoscopic assessment by protocol demonstrated mucosal inflammation characteristic of Crohn disease (CD) in up to one-third of patients with SpA. Video capsule endoscopy (CE) is a superior diagnostic tool to detect small bowel mucosal disease. Our study compared the accuracy of CE to standard colonoscopy for detection of inflammatory bowel lesions in patients with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 50 publications
2
38
0
Order By: Relevance
“…Based on their findings, the authors recommend endoscopic investigation of SpA patients with an elevated FC. Their observation is in keeping with our prospective SpACE Capsule study, which showed that FC was clinically useful in screening for IBD in established SpA 1 . We found that an elevated FC was associated with CD (OR 4.5, sensitivity 74%).…”
Section: To the Editorsupporting
confidence: 86%
See 2 more Smart Citations
“…Based on their findings, the authors recommend endoscopic investigation of SpA patients with an elevated FC. Their observation is in keeping with our prospective SpACE Capsule study, which showed that FC was clinically useful in screening for IBD in established SpA 1 . We found that an elevated FC was associated with CD (OR 4.5, sensitivity 74%).…”
Section: To the Editorsupporting
confidence: 86%
“…We are pleased to note the interest that Van Hoovels and colleagues have for our SpACE Capsule study 1 , and read with interest their investigation of the clinical utility of assaying fecal calprotectin (FC) to assist in the diagnosis of spondyloarthritis (SpA) 2 . Rheumatologists traditionally proclaim that the extraarticular manifestations of SpA include inflammatory bowel disease (IBD) 3 .…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…If endoscopy and histologic analysis reveal evidence of active CD, therapeutic management of patients with SpA could be changed, by choosing a treatment option that is effective for both CD and SpA (e.g., adalimumab, infliximab, ustekunimab) 10 . In the study by Kopylov, et al, the finding of CD led to a change in patient management in 65.2% of cases 1 . The guidance of SpA management based on FC results is promising and merits further investigation.…”
Section: Added Value Of Fecal Calprotectin To Support the Diagnosis Omentioning
confidence: 98%
“…We read with interest the article by Kopylov, et al, who reported small bowel inflammation consistent with Crohn disease (CD) in 42.2% of patients with spondyloarthropathy (SpA) by video capsule endoscopy 1 .…”
Section: Added Value Of Fecal Calprotectin To Support the Diagnosis Omentioning
confidence: 99%